2015
DOI: 10.1073/pnas.1518808112
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular density and normalization in response to neoadjuvant bevacizumab and chemotherapy in breast cancer patients

Abstract: Preoperative bevacizumab and chemotherapy may benefit a subset of breast cancer (BC) patients. To explore potential mechanisms of this benefit, we conducted a phase II study of neoadjuvant bevacizumab (single dose) followed by combined bevacizumab and adriamycin/cyclophosphamide/paclitaxel chemotherapy in HER2-negative BC. The regimen was well-tolerated and showed a higher rate of pathologic complete response (pCR) in triple-negative (TN)BC (11/21 patients or 52%, [95% confidence interval (CI): 30,74]) than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
170
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 62 publications
(60 reference statements)
12
170
0
Order By: Relevance
“…Within these perivascular segments, cells that were positive for either one or both pericyte markers were distinctly defined, namely Figure 1A and Supplemental Figure 1, A and B). While TNBC patients showed significantly higher MVD when compared with patients with luminal breast cancer ( Figure 1B), which is in agreement with previous reports (36) Figure 1C), thus indicating that a higher proportion of vessels in TNBC are immature with diminished pericyte coverage. Within each patient tumor evaluated, the MPI did not reflect a bias with respect to MVD, indicating that the computed pericyte coverage adequately reflects the heterogeneous composition of perivascular cells rather than reflecting overall low MVD (Supplemental Figure 1, C-F).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Within these perivascular segments, cells that were positive for either one or both pericyte markers were distinctly defined, namely Figure 1A and Supplemental Figure 1, A and B). While TNBC patients showed significantly higher MVD when compared with patients with luminal breast cancer ( Figure 1B), which is in agreement with previous reports (36) Figure 1C), thus indicating that a higher proportion of vessels in TNBC are immature with diminished pericyte coverage. Within each patient tumor evaluated, the MPI did not reflect a bias with respect to MVD, indicating that the computed pericyte coverage adequately reflects the heterogeneous composition of perivascular cells rather than reflecting overall low MVD (Supplemental Figure 1, C-F).…”
Section: Resultssupporting
confidence: 92%
“…Patients with triple-negative breast cancer (TNBC) may present with higher microvascular density (MVD), which possibly enhances their response to neoadjuvant anti-VEGF/bevacizumab therapy, which targets immature and newly formed blood vessels (36). However, the heterogeneous perivascular composition in subtypes of breast cancer remains undefined.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Avastintreated samples had a significant decrease of the signature 1 and 2 genes with a concomitant enrichment of signature 3 genes compared with vehicle samples. This analysis reveals the selective loss of less mature stroma (represented by signatures 1 and 2) upon treatment with anti-VEGF, consistent with prior preclinical and clinical studies (18)(19)(20)(21). Avastin only blocks human VEGF-A in this murine model, so we also explored an anti-mouse-VEGFA antibody (G6) in our Ad-VEGFA flank model.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, we observed differences in the frequency of stromal/vascular phenotypes between the two major histologies in gastric cancer, Lauren's "diffuse" and "intestinal" (Fig. 5A) (21). About 50% of intestinal-type gastric tumors contained predominantly immature stroma, as marked by high proportions of poorly lumenized CD34-postive vessels with little to no vWF staining (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…This observation is complex to explain within the context of the model of vascular normalization and the positive effects of adding bevacizumab to chemotherapy in lung cancer (39). Other studies suggest that antiangiogenic agents improve the perfusion (16,40,41); one of these studies showed an improved vascular network at the microscopic level in the patients that experienced favorable outcomes; however, the low number of patients and the nonrandomized nature of the study precludes definitive conclusions (40). We expected to observe a heterogeneous response, and that the patients showing improved oxygenation or hypoxia worsening would be those with better and worse outcomes respectively, as an indirect proof of vascular normalization.…”
Section: Discussionmentioning
confidence: 99%